Sie sind auf Seite 1von 5

# P/11/08/20

LÍMITES
𝟎 ∞
Indeterminaciones: =? ; =? ; ∞ − ∞ =? ; 𝟏∞ =? ; 𝟎𝟎 =?
𝟎 ∞

Ejercicios
𝑥 5 −32 25 −32 0
1) lim = = ?
𝑥→2 𝑥 2 +4𝑥−12 22 +4(2)−12 0

## 𝑥 5 −32 (𝑥−2)(𝑥 4 +𝑥 3 ∗2+𝑥 2 ∗22 +𝑥∗23 +24 )

lim 2 +4𝑥−12 =
𝑥→2 𝑥 (𝑥+6)(𝑥−2)

𝑥 5 −32 𝑥 4 +𝑥 3 ∗2+𝑥 2 ∗22 +𝑥∗23 +24 24 +(23 ∗2)+(22 ∗22 )+(2∗23) +24 80
lim 2 +4𝑥−12 = = = = 10
𝑥→2 𝑥 𝑥+6 2+6 8

## 𝑥 4 +𝑥 3 +𝑥 2 +𝑥−4 14 +13 +12 +1−4 0

2) lim = = ? Operación Auxiliar
𝑥→1 𝑥−1 1−1 0
Método de Ruffini
(𝑥−1)(𝑥 3 +2𝑥 2 +3𝑥+4)
lim
𝑥→1 𝑥−1 1 1 1 1 -4
1 1 2 3 4
lim (𝑥 3 + 2𝑥 2 + 3𝑥 + 4) = 13 + 2(1)2 + 3(1) + 4 = 10 1 2 3 4 0
𝑥→1

√𝑥−1−2 √5−1−2 0
3) lim = = ?
𝑥→5 𝑥−5 5−5 0
2
√𝑥−1−2 √𝑥−1+2 (√𝑥−1) −22 𝑥−1−4 𝑥−5
lim ∗ = (𝑥−5)( = (𝑥−5)( = (𝑥−5)(
𝑥→5 𝑥−5 √𝑥−1+2 √𝑥−1+2) √𝑥−1+2) √𝑥−1+2)

1 1 1
lim = =
𝑥→5 √𝑥−1+2 √5−1+2 4

3𝑥−√𝑥 2 +8 3(1)−√12 +8 0
4) lim = = ?
𝑥→1 2𝑥−√𝑥 2 +3 2(1)−√12 +3 0

## 3𝑥−√𝑥 2 +8 3𝑥+√𝑥 2 +8 2𝑥+√𝑥 2 +3

lim ∗ ∗
𝑥→1 2𝑥−√𝑥 2 +3 3𝑥+√𝑥 2 +8 2𝑥+√𝑥 2 +3

## 3𝑥−√𝑥 2 +8 3𝑥+√𝑥 2 +8 2𝑥+√𝑥 2 +3

lim ∗ ∗
𝑥→1 2𝑥−√𝑥 2 +3 3𝑥+√𝑥 2 +8 2𝑥+√𝑥 2 +3

## (3𝑥)2 −(√𝑥 2 +8 )2 2𝑥+√𝑥 2 +3

lim ∗
𝑥→1 (2𝑥)2 −(√𝑥 2 +3)2 3𝑥+√𝑥 2 +8

## 9𝑥 2 −(𝑥 2 +8) 2𝑥+√𝑥 2 +3

lim ∗
𝑥→1 4𝑥 2 −(𝑥 2 +3) 3𝑥+√𝑥 2 +8

9𝑥 2 −𝑥 2 −8 2𝑥+√𝑥 2 +3
lim ∗
𝑥→1 4𝑥 2 −𝑥 2 −3 3𝑥+√𝑥 2 +8

8𝑥 2 −8 2𝑥+√𝑥 2 +3
lim ∗
𝑥→1 3𝑥 2 −3 3𝑥+√𝑥 2 +8

## 8(𝑥 2 −1) 2𝑥+√𝑥 2 +3

lim ∗
𝑥→1 3(𝑥 2 −1) 3𝑥+√𝑥 2 +8

8 2𝑥+√𝑥 2 +3
lim ∗
𝑥→1 3 3𝑥+√𝑥 2 +8

8 2(1)+√12 +3
= ∗
3 3(1)+√12 +8
8 2+2
= ∗
3 3+3
8 4
= ∗
3 6
32
=
18
16
=
9
5 5
√2𝑥−5− √2𝑥−5 √2(3)−5 − √2(3)−5 0
5) lim = = ?
𝑥→3 𝑥−3 3−3 0

5
√2𝑥−5− √2𝑥−5
lim
𝑥→3 𝑥−3

Cambio de variable

## 𝑢10 = 2𝑥 − 5 𝑢10 = 2𝑥 − 5 𝑢10 = 2𝑥 − 5

−2𝑥 = −5 − 𝑢10 (-1)
𝑠𝑖 𝑥 → 3 𝑢10 = 2(3) − 5
2𝑥 = 5 + 𝑢10
𝑢10 = 1
10 10 5 + 𝑢10
√𝑢10 = √1 𝑥=
𝑢=1 2

5
√𝑢10 − √𝑢10
lim
𝑢→1 5 + 𝑢10
−3
2
𝑢5 − 𝑢2
lim
𝑢→1 5 + 𝑢10 − 6
2
𝑢5 − 𝑢2
lim
𝑢→1 𝑢10 − 1
2
2(𝑢5 − 𝑢2 )
lim
𝑢→1 𝑢10 − 1
2𝑢2 (𝑢3 − 1)
lim
𝑢→1 𝑢10 − 1
2𝑢2 (𝑢 − 1)(𝑢2 + 𝑢 + 1)
lim
𝑢→1 (𝑢 − 1)(𝑢9 + 𝑢8 + 𝑢7 + 𝑢6 + 𝑢5 + 𝑢4 + 𝑢3 + 𝑢2 + 𝑢 + 1)

2𝑢2 (𝑢2 + 𝑢 + 1)
lim
𝑢→1 (𝑢9 + 𝑢8 + 𝑢7 + 𝑢6 + 𝑢5 + 𝑢4 + 𝑢3 + 𝑢2 + 𝑢 + 1)

2(1)2 (12 + 1 + 1)
=
(19 + 18 + 17 + 16 + 15 + 14 + 13 + 12 + 1 + 1)
6
=
10
3
=
5
Resolver los siguientes límites
𝑥 2 +𝑥+3 ∞
1) lim √(𝑥−1)(𝑥+1) = ∞ ?
𝑥→∞

𝑥2 +𝑥+3
𝑥2
lim √ 𝑥2 −1
𝑥→∞
𝑥2

𝑥2 𝑥 3
+ +
𝑥2 𝑥2 𝑥2
lim √ 𝑥2 1
𝑥→∞ −
𝑥2 𝑥2

13 1 3
1+𝑥+ 1+∞+∞
𝑥2
lim √ 1 =√ 1 =1
𝑥→∞ 1− 2 1−∞
𝑥

## 2) lim √5𝑥 + 3 − √3𝑥 = ∞ − ∞ ?

𝑥→∞

√5𝑥+3+√3𝑥
lim (√5𝑥 + 3 − √3𝑥) ∗
𝑥→∞ √5𝑥+3+√3𝑥

(√5𝑥+3)2 −(√3𝑥)2
lim
𝑥→∞ √5𝑥+3+√3𝑥
5𝑥+3−3𝑥 2𝑥+3
lim = lim
𝑥→∞ √5𝑥+3+√3𝑥 𝑥→∞ √5𝑥+3+√3𝑥
2𝑥+3

lim 𝑥
√5𝑥+3−√3𝑥
𝑥→∞
𝑥

2𝑥 3
+
lim 𝑥 𝑥
𝑥→∞ √5𝑥+3+ √3𝑥
𝑥 𝑥

3
2+𝑥
lim
𝑥→∞ √5𝑥+3+√ 3𝑥
𝑥2 𝑥2

3
2+𝑥
lim
𝑥→∞ √ 5𝑥+ 3 +√ 3𝑥
𝑥2 𝑥2 𝑥2

3
2+𝑥
lim
𝑥→∞ √5+ 3 +√3
𝑥 𝑥2 𝑥

3
2+∞ 2
lim = =∞
𝑥→∞ √ 5 + 3 +√ 3 0
∞ ∞ ∞
3 1
1+8𝑥 ∞
3) lim ( ) =1𝑥 ? lim (1 + 𝑥) = 𝑒
𝑥
𝑥→0 1+7𝑥 𝑥→0
3
3
1+8𝑥 (1+8𝑥)𝑥
lim ( ) = 𝑥 3
𝑥→0 1+7𝑥 (1+7𝑥)𝑥
3 8
∗8
(1+8𝑥)𝑥
lim 3 7
𝑥→0 (1+7𝑥)𝑥∗7

1 3∗8
∗ 1
(1+8𝑥)8𝑥
lim 1 3∗7
𝑥→0 (1+7𝑥)7𝑥∗ 1

1 3∗8
[(1+8𝑥)8𝑥 ] 𝑒 24
lim 1 3∗7
= 𝑒 21 = 𝑒 24 ∗ 𝑒 −21 = 𝑒 3
𝑥→0
[(1+7𝑥)7𝑥 ]

7𝑥 −5𝑥 0 𝑎𝑥 −1
4) lim (4 𝑥−3𝑥 ) = 0 ? lim 𝑥
= 𝑙𝑛𝑎
𝑥→0 𝑥→0
7𝑥 −5𝑥 +1−1
lim (4 𝑥−3𝑥+1−1)
𝑥→0
(7𝑥 −1)−(5𝑥 −1)
lim
𝑥→0 (4 𝑥 −1)−(3𝑥 −1)
(7𝑥 −1)−(5𝑥 −1)

lim 𝑥
(4𝑥 −1)−(3𝑥 −1)
𝑥→0
𝑥

## (7𝑥 −1) (5𝑥 −1)

− 𝑥 𝑙𝑛7−𝑙𝑛5
lim 𝑥
(4𝑥 −1) (3𝑥 −1) = 𝑙𝑛4−𝑙𝑛3
𝑥→0 − 𝑥
𝑥

𝑠𝑒𝑛7𝑥+𝑠𝑒𝑛5𝑥 0
5) lim = ?
𝑥→0 𝑠𝑒𝑛3𝑥+𝑥 0
𝑠𝑒𝑛7𝑥 𝑠𝑒𝑛5𝑥
+ 𝑥
lim 𝑥
𝑠𝑒𝑛3𝑥 𝑥
𝑥→0 +𝑥
𝑥

𝑠𝑒𝑛7𝑥∗7 𝑠𝑒𝑛5𝑥∗5
+ 5𝑥 𝑠𝑒𝑛𝑥
lim 7𝑥
𝑠𝑒𝑛3𝑥∗3 lim =1
𝑥→0 +1 𝑥→0 𝑥
3𝑥

7+5 12
= 3+1 = =3
4

𝑒 2𝑥 −1 0
6) lim 𝑠𝑒𝑛3𝑥 = 0 ?
𝑥→0
𝑒2𝑥 −1

lim 𝑥
𝑠𝑒𝑛3𝑥
𝑥→0 𝑥
(𝑒𝑥 )2 −1
𝑙𝑛𝑒 2 2𝑙𝑛𝑒 2
lim 𝑥
𝑠𝑒𝑛3𝑥∗3 = = =3
𝑥→0 3 3
3𝑥

𝑠𝑒𝑛2 𝑥 0
7) lim 1−𝑐𝑜𝑠𝑥 = 0 ?
𝑥→0

1−𝑐𝑜𝑠 2 𝑥
lim 𝑠𝑒𝑛2 𝑥 + 𝑐𝑜𝑠 2 𝑥 = 1
𝑥→0 1−𝑐𝑜𝑠𝑥
(1−𝑐𝑜𝑠𝑥)(1+𝑐𝑜𝑠𝑥)
lim
𝑥→0 1−𝑐𝑜𝑠𝑥

## lim (1 + 𝑐𝑜𝑠𝑥) = 1 + 𝑐𝑜𝑠0 = 1 + 1 = 2

𝑥→0
𝑡𝑎𝑛𝑥−𝑠𝑒𝑛𝑥 0
8) lim =0 ?
𝑥→0 𝑥3
𝑠𝑒𝑛𝑥
−𝑠𝑒𝑛𝑥
lim 𝑐𝑜𝑠𝑥
𝑥→0 𝑥3
𝑠𝑒𝑛𝑥−𝑐𝑜𝑠𝑥∗𝑠𝑒𝑛𝑥

lim 𝑐𝑜𝑠𝑥
𝑥→0 𝑥3
𝑠𝑒𝑛𝑥−𝑐𝑜𝑠𝑥∗𝑠𝑒𝑛𝑥
lim
𝑥→0 𝑥 3 𝑐𝑜𝑠𝑥

𝑠𝑒𝑛𝑥(1−𝑐𝑜𝑠𝑥)
lim
𝑥→0 𝑥 3 𝑐𝑜𝑠𝑥

𝑠𝑒𝑛𝑥(1−𝑐𝑜𝑠𝑥) (1+𝑐𝑜𝑠𝑥)
lim ∗ (1+𝑐𝑜𝑠𝑥)
𝑥→0 𝑥 3 𝑐𝑜𝑠𝑥

𝑠𝑒𝑛𝑥(1−𝑐𝑜𝑠 2 𝑥)
lim 𝑥 3 𝑐𝑜𝑠𝑥(1+𝑐𝑜𝑠𝑥) 𝑠𝑒𝑛2 𝑥 + 𝑐𝑜𝑠 2 𝑥 = 1
𝑥→0

𝑠𝑒𝑛𝑥∗𝑠𝑒𝑛2 𝑥
lim
𝑥→0 𝑥 3 𝑐𝑜𝑠𝑥(1+𝑐𝑜𝑠𝑥)
𝑠𝑒𝑛𝑥 𝑠𝑒𝑛𝑥 𝑠𝑒𝑛𝑥 1
lim ( 𝑥
)( 𝑥
)(
𝑥
)∗
𝑐𝑜𝑠𝑥(1+𝑐𝑜𝑠𝑥)
𝑥→0
1 1
= =
𝑐𝑜𝑠0(1+𝑐𝑜𝑠0) 2